(3GdhGaj aj fXe GdbhGajs - (3GdQfOj , UGdM Hf jRjO Hf UGdM Hf ehSi Hf CHj GdbGSe Hf Ydj Hf TQja GdfaRj, CHh GdWjH CHh GdHbGA,J (B684 (3g` s
(3ChdgG (B:s
(3hbO ChQOJ aj cJGHg gPG LedI cGajI s
(3BNQgG (B:s
(3haYdf HSchf GdYjf hMQcJgG ced GdLRA GdQGHY ef cJGH GdhGaj aj fXe GdbhGaj s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais